Development of Tutorial Video Media on PPE Us in Food Processing Practices at the PVKK FKIP UST - Eko Sri Wahyuningsih; Rina Setyaningsih; Ika Wahyu Kusuma Wati (Jurnal Pendidikan Tata Boga dan Teknologi, 2026)
This study aims to develop instructional media in the form of a video tutorial on the use of Personal Protective Equipment (PPE) in food-processing practice, to determine the feasibility of the PPE tutorial video, and to identify students’ responses to the video tutorial in food-processing practicum learning. This research is a Research and Development (R&D) study using the Four-D (4D) development model, which consists of the define, design, development, and dissemination stages. The research subjects were third-semester Culinary Arts students enrolled in the Food-Processing Technology Management course in the PVKK Study Program, FKIP UST. The feasibility assessment of the learning media was carried out by media experts and material experts. The small-scale trial involved 5 students, while the limited-scale trial involved 23 students. The instrument used was a questionnaire, and the data analysis technique employed was quantitative descriptive analysis. The results showed that the PPE tutorial video for food-processing practice has a duration of 10 minutes and 2 seconds and can be accessed anytime and anywhere through the YouTube link https://bit.ly/VideoTutorialAPD. The tutorial video was declared highly feasible by material experts with a score of 90.83% and by media experts with a score of 94.17%. Student responses to the PPE tutorial video during the small-scale trial yielded a percentage of 93.61% (strongly agree), and the limited-scale trial yielded a percentage of 87.74% (strongly agree).